O dialogismo em slogans brasileiros de cervejas do século XXI - Montesanti, Adriana Pernambuco (2013)
Beer’s slogans in Brazil have been pleased viewers and awaken researchers’ curiosity for the creativity and originality they have. Therefore, it is relevant to observe what is underlying the imagery construction of these slogans and the text that they convey. This report aimed to analyse the discursive constructions and the voices which are present in beer’s slogans of the 21st Century, conveyed through the media. The specific aim was to verify the use of female image in the slogan, in search of detecting the presence of woman’s body exploration to attract male attention and increase the alcoholic drink consumption. The reason of this report is due to the necessity of verification, concerned the issue if the predominant presence of women figure in advertisements is direct linked to a speech which is predominantly masculine over the feminine figure. The theoretical framework will be comprised of reflections and discoveries of Bakhtin (1997; 2003; 2010), concerned the dialogism and polyphony, as well as the studies of Fiorin (2006), Koch (2002), Brait (2003, 2007, 2011) and Barros (2003). The theoretical background was sought to sustain the analyses of each slogan, observing the dialogic relations that exists among them and the effects of meaning concerned the use of female image by the advertisement agencies and conveyed in the media. The methodological procedure consisted in to analyse five Brazilian beer’s slogans, from the year 2000 up to nowadays. The corpus was collected through advertisements in magazines, television and specific companies’ websites of some brands and marketing companies involved. The slogans used on this report were, placed by order: 1) Devassa “Todo mundo tem um lado Devassa”; 2) Antarctica “Boa, só se for Antarctica”; 3) Skol A cerveja que desce redondo; 4) Kaiser, “Essa é gostosa!; 5) Bavária: Não beba só uma, Bebavárias, 6) “Para bom bebedor, Meia palavra basta; Schin 7)“Cervejão”; Brahma: “Refresca até pensamento”, Esquadrão refresca” 8) Com Glacial tem jogo, “Com Glacial o verão vira diversão”, “Cerveja Glacial combina com tudo” - Se tem glacial tem jogo”, “glacial essa é sensacional”, 9) “Cerveja Colônia - slogans : é Disso que eu gosto e essa pegou”. Keywords : dialogism; discursive gender; slogans; beer; 21st Century.